(untitled) (Update Dental College Journal, 2018)
Background: This paper reviews the types, prevalence and demographic distribution of maxillofacial tumors, cysts and tumor-like lesions in a Bangladeshiteaching Hospital.An observational descriptive study (January’ 2014 to December’ 2016) was performed at Oral and Maxillofacial Surgery depart- ment, Dental Unit,TMSS Medical College and Hospital. This study presents 55 cases of maxillofacial tumour & tumour like lesions collected over 3 years at a tertiary oral care centre in Bogra, Bangla- desh. Objectives:To find out the distribution & pattern of maxillofacial tumours and to find out the age, sex, site, clinical presentation and thehistological types of these tumors Method: A cross sectional descriptive study where the Histopathological types of the maxillofacial tumours were analyzed to indicate the numbers that occurred and also the pattern of occurrence according to age, gender, site and clinical presentation. Result: There were 55 maxillofacial tumour & tumour like lesions of which 44 (80.01%) were Benign tumours & 11 (19.81%) were malignant tumours. Among Eighteen histo- pathologic types were found of which Squamous cell carcinoma (18.18%), Ameloblastoma (16.36%), Odontogenic keratocystic tumour (10.90%), Dentigerous cyst (7.27%)& Radicular cyst (7.27%) were predominant. The male to female ratio was 1.29:1. Patients were between 10 years and 72 years with most patients (27.27%) in 51 to 60 years of life. Case presented with symptoms such as swelling (41.96%), pain (28.82%) and loosetooth (17.12%). Conclusion: Both malignant and benign tumours are seen. In the present study, SCC and ameloblastoma were the commonest malignant and benign odontogenic tumours seen respectively; the two representing more than 34.54% of all tumors.Tumour & tumour like lesions of the oral & maxillofacial region with late presentation still remains the main challenging factor in the early detection & management. Surgery was the main modality used for treat- ment while some patients had no treatment due to self discharge and late presentation. Update Dent. Coll. j: 2018; 8 (1): 22-28